Simultaneous Integration of Kyber and Dilithium on Embedded Microcontrollers: Towards Quantum-Resistant IoT Systems - Do, Thi-Bac; Dinh, Khanh-Linh (Engineering, Technology & Applied Science Research, 2026)
The rapid progress of quantum computing poses a serious threat to conventional public-key cryptographic schemes such as Rivest–Shamir–Adleman (RSA) and Elliptic Curve Cryptography (ECC), particularly in resource-constrained Internet of Things (IoT) environments. In response, Post-Quantum Cryptography (PQC) algorithms based on lattice problems—most notably Kyber for key encapsulation and Dilithium for digital signatures—have been standardized by the U.S. National Institute of Standards and Technology (NIST). While these schemes offer strong security guarantees, their practical deployment on low-power embedded microcontrollers remains challenging due to strict constraints on memory, computation time, and energy consumption. This paper presents a system-level and simultaneous integration of Kyber and Dilithium on the ESP32 microcontroller platform. To enable the concurrent execution of both NIST-standardized primitives, we apply a set of software-level optimization techniques, including Barrett reduction for efficient modular arithmetic, buffer reuse to minimize memory footprint, and careful local variable management to reduce stack usage. Unlike prior studies that typically evaluate post-quantum primitives in isolation or rely on simulated environments, our work provides an empirical evaluation based on real hardware measurements. Experimental results obtained on an ESP32 DevKit demonstrate that optimized implementations of Kyber and Dilithium can coexist reliably within the platform’s limited resources, achieving practical execution times and acceptable energy consumption for embedded IoT applications. These findings provide concrete evidence that quantum-resistant public-key cryptography can be feasibly deployed on widely used microcontroller-based systems, thereby supporting the transition toward secure and future-proof IoT infrastructures.